Women on Boards of Directors: Is It Possible to Exist in Old Boys’ Club? - Bursali, Yeliz Mohan (European Scientific Journal, ESJ, 2017)
Women are not/cannot be represented sufficiently in managerial positions in business world in Turkey and around the world, and we can state that the ratio of women representation on boards of directors is even lower. In line with the idea that companies should be managed in a more corporate way, issues of gender diversity and women members of boards of directors have started to be discussed more and more in recent years, leading both legal and voluntary works to come into effect. Various studies on the presence of women members on boards of directors in the world and in Turkey reveal that the representation of women is not at the desired level for an effective board of directors. Focused on some studies and reports in the world and in Turkey, the present study aims to reveal the condition of female members on boards of directors in quantitative terms and generally discuss the contributions that more female members would make to boards of directors. Although some countries including Turkey have relatively good ratios of female members on boards of directors and have made a little progress in the subject, the numbers are still quite insufficient in terms of the effective board of directors and good governance. Women can bring different points of view than men can to the board of directors and thus to the company management, and it is not only a need but also a necessity to conduct more work, on legal and voluntary basis, in order to benefit from women’s knowledge, skills and insights.